Estimating prevalence rates of migraine and tension-type headache among the students of Shiraz university of medical sciences - S.M.T Ayatolahi; T Darabzand; F Bozorgi; F Shibani-Monfared (Journal of Kerman University of Medical Sciences, 1999)
this study investigated the prevalence rates of migrine and tension-type headaches among the students of Shiraz university of medical sciences during the academic year 1996-1997.the study was carried out cross-sectionally on a representative random sample of 310 students selected systematically.A semi structured questionnaire was used to screen headache among the students,applying the international Headache society Classification.A total of 123(39.7%) students were screened for headache and examined clinically for a proper diagnosis.as a result 80(25.8%) students were diagnosed to have migraine,tension-type headache or coexiting migraine and tension-headache.prevalence rates for tension-headache,migraine,coexisting tension-headache and migraine were 15.5%,7.4% and 2.6% respectively.odds ratio of tension-headache in boys was 3.4 times higher than that of girls,(p<0.01),but it was not statistically different for migraine and coexisting migraine and tension-headache.the relationship between the headaches and sevral factors were examined and significant associations were found between migraine and coexisting migraine and tension-type headache with sleeping pattern of students(p<0.05).the odds ratio of migraine in students who had abnormal sleeping pattern was 2.5 times higher than those with normal sleeping pattern,but for coexisting migraine and tension-headache with regard to sleeping pattern it was estimated to be 7.8 times higher than normal.both odds ration were statistically significant(p<0.05).in general,headaches including migraine.tension-type,etc were significantly associated with family history of headache (p<0.001)